Isolation and functional characterization of an acidic myotoxic phospholipase A2 from colombian Bothrops asper venom - Arias, Silvia Posada (2017)
Myotoxic phospholipases A2 (PLA2) are responsible for many clinical manifestations in envenomation by Bothrops snakes. A new myotoxic acidic Asp49 PLA2 (BaCol PLA2) was isolated from Colombian Bothrops asper venom using reverse-phase high performance liquid chromatography (RP-HPLC). BaCol PLA2 had a molecular mass of 14,180.69 Da (by mass spectrometry) and an isoelectric point of 4.4. The complete amino acid sequence was obtained by cDNA cloning (GenBank accession No. MF319968) and revealed a mature product of 124 amino acids with Asp at position 49. BaCol PLA2 showed structural homology with other acidic PLA2 isolated from Bothrops venoms, including a non-myotoxic PLA2 from Costa Rican B. asper. In vitro studies showed cell membrane damage without exposure of phosphatidylserine, an early apoptosis hallmark. BaCol PLA2 had high indirect hemolytic activity and moderate anticoagulant action. In mice, BaCol PLA2 caused marked edema and myotoxicity, the latter seen as an increase in plasma creatine kinase and histological damage to gastrocnemius muscle fibers that included vacuolization and hyalinization necrosis of the sarcoplasm.